Clinically Healthy Human Gingival Tissues Show Significant Inter-individual Variability in GCF Chemokine Expression and Subgingival Plaque Microbial Composition - Bamashmous, Shatha; Kotsakis, Georgios A.; Jain, Sumita; Chang, Ana M.; McLean, Jeffrey S.; Darveau, Richard P. (Frontiers in Oral Health, 2021)
Aim: Clinically healthy gingival tissue is maintained through precise and controlled regulation of host defense mechanisms that protects gingival tissue in the presence of commensal bacterial colonization. However, variability in the expression of healthy immune-surveillance mediators across gingival and periodontally healthy individuals has yet to be reported. Therefore, this cross-sectional study examines the inter-individual variability in key health mediators within gingival crevicular fluid in relation to the sub-gingival plaque microbiome. Methods: A multiplex immunoassay of 40 chemokines were carried out using gingival crevicular fluid collected from 20 healthy human subjects aged 12-17 years old. In addition, neutrophils were indirectly measured by myeloperoxidase using traditional ELISA. Lastly, sub-gingival plaque was characterized with the Illumina Miseq targeting the 16S rRNA gene. Results: In health, there were distinct variations within individual gingival crevicular fluid chemokine profiles, as well as in the presence of neutrophils, that divided the test subjects into two groups. Similarly, the sub-gingival plaque microbiome analysis revealed two additional groups that did not correlate with the chemokine groups identified. Conclusion: The lack of concordance between the microbial composition and chemokine profile during health may be a reflection of the unique microbial composition of each individual coupled with variations within their host response, emphasizing the vast complexity of the defense mechanisms in place to maintain gingival health.